The post-Soviet evolution of the Russian urban system. Issue 1 (2nd January 2017) - Kolomak, Evgeniya
ABSTRACT: An analysis of annual: city size data for more than 1000 cities in the period of transition from a planned to a market economy in 1991–2013 shows that: 1) predictions of the rapid growth of the urban system and of primary cities due to the introduction of market forces are not confirmed; 2) the city size distribution is almost unchanged; and 3) regression estimates reveal the significance of agglomeration economies. The results are consistent with the theories of random growth, increasing returns and locational fundamentals, but provide no convincing evidence for multiple spatial equilibria.